Study on the Interference of Iron, Aluminium and Silicon on the Atomic Absorption Spectrometric Determination of Mangan in Laterite Mineral - Sulistyo Saputro; Ngatidjo Hadipranoto; Agus Kuncaka (Indonesian Journal of Chemistry, 2001)
Interference of iron, aluminum and silicon on the determination of mangan in laterite mineral by atomic absorption spectrometry has been investigated. Dissolution of laterite mineral into solution have been carried out by wet method destruction using combination of 7 mL of aquaregia, 7.5 mL of concentrated perchloric acid and 9 mL of fluoride acid 48% In sealed teflon flask heated at temperature of about 110 °C for 3 hours to determine the content of Mn element in laterite mineral directly. Interference of these three metals were carried out by evaluating the differences of Mn absorbance at wavelength 279.50 nm and slit width 0.2 nm between the solutions containing mangan only and those containing the some amount of mangan together with the interfering elements at those concentration range in laterite mineral. The result showed that both iron at concentration of 100 ppm until 500 ppm and aluminum at concentration at 3 ppm until 15 ppm caused significant and non-linear interference on the determination of Mn 2 ppm. Interference of iron was effectively eliminated by releasing action of aluminum. The signal depression reductional decrease due to 234 ppm of silicon on the determination of Mn 2 ppm can be eliminated by adding 2.30 mL of CaCl2 0.2% (m/v) into these solution. The content of Mn in the laterite mineral after and before adding of CaCl2 into solution were 2407.04 ± 59.26 μg g-1 and 2311.76 ± 23.61 μg g-1, respectively. This result was significantly different at confidence level 95% as shown by the value of tcalculated=4.91 that was higher than ttable=4.30.